Governance and Innovation in Muhammadiyah Universities in Indonesia: A Literature-Based Mapping of Organizational Competitiveness - Prakoso, Velandani; Kurniawan, Bachtiar Dwi (Department of Government Studies, Universitas Muhammadiyah Buton., 2025)
Muhammadiyah Universities in Indonesia face increasing demands to enhance institutional competitiveness, governance quality, and innovation capacity in response to digital transformation and global educational shifts. Despite numerous studies on leadership models, quality management, and technology integration, the academic literature remains fragmented and lacks a comprehensive thematic and conceptual mapping. This study aims to address that gap by systematically analyzing the evolution of governance and innovation topics in Muhammadiyah Universities over the past decade. Using a bibliometric approach based on Scopus data, the research applied the PRISMA protocol to ensure transparency in literature selection and employed RStudio-Biblioshiny and CiteSpace for data processing and visualization. A total of 214 peer-reviewed journal articles published between 2011 and 2024 were analyzed to identify dominant themes, citation bursts, and thematic clusters. The results reveal that topics such as “Higher Education,” “Muhammadiyah,” and “Organizational Commitment” form the conceptual core, while emerging themes like “Social Media,” “Student,” and “Education” reflect a shift toward participatory and digital strategies. Citation burst analysis highlights growing attention to “Employee Performance” and “Classroom Management,” indicating a strategic focus on human resource development. The study concludes that governance and innovation at Muhammadiyah Universities are multidimensional, involving policy, technology, organizational culture, and Islamic values. These findings provide an empirical foundation for evidence-based institutional strategies and open pathways for future exploration of inclusive and adaptive governance models aligned with the challenges of educational disruption.